1980
DOI: 10.1039/dt9800002032
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal binding sites and ligand parameters

Abstract: N3-Ligdnd constant, PL/V ( & 0.05 V cstimated error) + 1.46 1.40 0.00 -0.07 -0.10 -0.35 -0.38 -0.40 -0.4:) -0.58 -0.59 -0.77 -0.78 -0.88 -1.00 -1.16 -1.15 -1.17-1.19 -1.22 -1.26 -1.55measured and values which we have deduced by intcrpolation from data from other series of Complexes (see below). These ligand constants refer t o L as a twoelectron donor ligand which must be added t o the 16electron moiety to give the closed-shell 18-electron complexes [M,L], x bonding being ignored. Considered in this way the ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
1
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(159 citation statements)
references
References 0 publications
9
148
1
1
Order By: Relevance
“…This increase is attributed to the π and σ interactions of ligand L with metal; thus, for ruthenium, unsaturated ligands stabilize the lowest oxidation state. Chatt et al [18] observe the effect of the ligands on the metal atom, similar to that observed for aromatic compounds using cyclic voltammetry. These studies show that the higher the reception capability of electrons π is allied to the smaller capacity σ of ligand L, the greater the value of the formal charge E f will be.…”
supporting
confidence: 62%
“…This increase is attributed to the π and σ interactions of ligand L with metal; thus, for ruthenium, unsaturated ligands stabilize the lowest oxidation state. Chatt et al [18] observe the effect of the ligands on the metal atom, similar to that observed for aromatic compounds using cyclic voltammetry. These studies show that the higher the reception capability of electrons π is allied to the smaller capacity σ of ligand L, the greater the value of the formal charge E f will be.…”
supporting
confidence: 62%
“…By applying the previously reported [2] Es and 8 parameters for the iron site of this study {FeH(dppe)2} + (Es = 1.04, p = 1.0), it was possible to estimate the PL parameter for CN as well as for the cyano-derived ligands (Table), Another electrochemical parametrization approach was developed by Lever [4,5] who proposed a general redox potential-structure relationship expressed by eq. Alternatively, from the above PL values of the isocyanide ligands, one could also try to estimate the Lever EL values by taking into account the observed [4] overall linear relationship (except for carbon monoxide [4] and other strong it-electron acceptors such as carbynes [6]) between the two parameters [eq.…”
Section: Resultsmentioning
confidence: 99%
“…2) by the oxidation potential of its carbonyl complex [Ms(CO)] (the higher Es the lower the electron-richness), whereas p is a measure of the polarisability of the metal site [2]. PL is defined as the difference…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A ligan parameter, PL was defined (10, 12,131 where, for example, v1.02 Sintra.doc march 15/92 --2--PL -Ev2(Cr(CO) 6 1 -EV2[Cr(CO) 5 L! (2) with some additional refinements to which the reader is referred [111.…”
Section: Le In This Caseixeel(l))] -X El(x) + Y El(y) + Z El(z)mentioning
confidence: 99%